Improving Volleyball Lower Serve Ability after Push-Up and Pull-Up Training for 6 Weeks in Junior High School Students - Umdah, Barirohtul; Handayani, Heni Yuli; Widodo, Haryo Mukti; Purwoto, Septyaningrum Putri (Universitas Negeri Surabaya, 2023)
This research aims to improve the volleyball bottom serve ability by applying push-up and pull-up exercises to NU Arosbaya Middle School students. The method used in this research is quantitative with an experimental approach. A sample of 20 male students was taken using probability sampling with simple random sampling. The research design used is a true experimental design. The research uses a true experimental design, namely, a pretest-posttest control group design. This research instrument determines the bottom serviceability using the bottom service test. This research was conducted for six weeks, with training carried out one week three times. From the descriptive test results, the pre-test has a value of 16.25, and the post-test post-test results have a value of 24.25. From the paired sample t-test results, the t-count value was -11.830 and a sig (2-tiled) of 0.00. Because the sig value is < 5% (a), it can be concluded that there is a difference in the pre-test and post-test post-test scores. This research concludes that push-up exercises and pull-up exercises have a significant influence on improving the volleyball bottom serve ability of NU Arosbaya Middle School students.